Youths' and Parents' Experiences and Perceived Effects of Internet-Based Cognitive Behavioral Therapy for Anxiety Disorders in Primary Care: Mixed Methods Study - Josefine Lotten Lilja; Mirna Rupcic Ljustina; Linnea Nissling; Anna Caroline Larsson; Sandra Weineland (JMIR Publications, 2021)
BackgroundAnxiety is common among youths in primary care. Face-to-face treatment has been the first choice for clinicians, but during the COVID-19 pandemic, digital psychological interventions have substantially increased. Few studies have examined young people's interest in internet treatment or the attitudes they and their parents have toward it. ObjectiveThis study aims to investigate adolescents' and parents' attitudes toward and experiences of internet-based cognitive behavioral anxiety treatment in primary care and its presumptive effects. MethodsThe study used mixed methods, analyzing qualitative data thematically and quantitative data with nonparametric analysis. Participants were 14 adolescents and 14 parents recruited in adolescent primary health care clinics. The adolescents and their parents filled out mental health questionnaires before and after treatment, and were interviewed during ongoing treatment. ResultsThe quantitative data indicated that the internet-delivered cognitive behavioral therapy program used in this study was successful in reducing symptoms (χ22=8.333; P=.02) and that adolescents' motivation is essential to the treatment outcome (r=0.58; P=.03). The qualitative results show that youths highly value their independence and freedom to organize treatment work on their own terms. The parents expressed uncertainty about their role and how to support their child in treatment. It was important for parents to respect the youths' need for autonomy while also engaging with them in the treatment work. ConclusionsInternet treatment in primary care is accepted by both youths and their parents, who need clarification about the difference between their role and the therapist's role. Patient motivation should be considered before treatment, and therapists need to continue to develop the virtual alliance. Finally, primary care should be clearer in informing adolescents and their parents about the possibility of internet treatment.